1997
DOI: 10.1095/biolreprod56.2.495
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Gene Transfer to rat Testis in Vivo

Abstract: To study transgene expression in the adult rat testis in vivo, an adenovirus vector carrying a lacZ transgene with a nuclear localization signal was used as a marker. The adenovirus vector was first tested on rat Sertoli cell-germ cell cocultures in vitro; it efficiently mediated transgene expression in Sertoli cells but not germ cells. This vector was then delivered to the interstitial compartment of adult rat testes by intratesticular injection, resulting in Leydig cells expressing the transgene. Alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
61
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 0 publications
6
61
3
Order By: Relevance
“…We extended the findings reported in other studies (18) by demonstrating that adenoviruses could be used to infect Sertoli cells in infertile mouse testes. Furthermore, we found that the introduction of full-length Sl factor cDNA into the Sertoli cells partially restored spermatogenesis up to round spermatid stage in the Sl͞Sl d testes, and offspring were produced after microinsemination.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…We extended the findings reported in other studies (18) by demonstrating that adenoviruses could be used to infect Sertoli cells in infertile mouse testes. Furthermore, we found that the introduction of full-length Sl factor cDNA into the Sertoli cells partially restored spermatogenesis up to round spermatid stage in the Sl͞Sl d testes, and offspring were produced after microinsemination.…”
Section: Discussionsupporting
confidence: 82%
“…Earlier attempts at using adenoviruses to infect Sertoli cells in wild-type testes had limited success; transgene expression lasted for a few weeks and was accompanied by a severe inflammatory reaction (18). In contrast, our results show that infected Sertoli cells in germ cell-depleted testes continued to express the LacZ gene for up to 3 mo.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations